1996
DOI: 10.1095/biolreprod55.5.1133
|View full text |Cite
|
Sign up to set email alerts
|

Regionalization and Redistribution of Membrane Phospholipids and Cholesterol in Mouse Spermatozoa during in Vitro Capacitation1

Abstract: Fracture-label, surface-replica, and routine freeze-fracture techniques were used in combination with phospholipase A2-colloidal gold (PLA2-CG) and filipin as probes to study changes in the distribution of phospholipids and cholesterol, respectively, in morphologically defined plasma membrane domains of mouse spermatozoa during in vitro capacitation. In noncapacitated spermatozoa, quantitative analysis revealed that the fractured plasma membrane overlying the equatorial segment carried the highest PLA2-CG labe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 31 publications
5
44
0
1
Order By: Relevance
“…27 In our ASM-deficient mice, lipid accumulation was histologically evident in somatic cells of the gonads (Figure 1), as well as in fully formed caudal spermatozoa ( Figure 2). Cholesterol has been localized to the acrosome region of the sperm head and the tail midpiece, 29,30 and our data showed that spermatozoa from ASMKO mice had an increase in filipin-sterol complexes over the acrosome (Figure 3, A and B).…”
Section: Effect Of Spm Accumulation On Cholesterol Efflux Acrosome Rmentioning
confidence: 57%
“…27 In our ASM-deficient mice, lipid accumulation was histologically evident in somatic cells of the gonads (Figure 1), as well as in fully formed caudal spermatozoa ( Figure 2). Cholesterol has been localized to the acrosome region of the sperm head and the tail midpiece, 29,30 and our data showed that spermatozoa from ASMKO mice had an increase in filipin-sterol complexes over the acrosome (Figure 3, A and B).…”
Section: Effect Of Spm Accumulation On Cholesterol Efflux Acrosome Rmentioning
confidence: 57%
“…Moreover the cholesterol distinctively distributes in the plasma membrane over the acrosomal region [19−22]. In conventional IVF, these components never enter the oocyte because the cholesterol is dissociated from the acrosomal plasma membrane during sperm capacitation [20,21,23] and the acrosome breaks down immediately before oocyte penetration [24].…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol effl ux is promoted by albumin ( Fig. 2 ) and high bicarbonate levels, which facilitate lipoprotein-mediated cholesterol effl ux (77)(78)(79). Cholesterol removal was restricted only to the nonraft membrane fraction of the sperm plasma membrane, whereas the content of cholesterol in the raft membrane fraction remained unchanged ( 75 ).…”
Section: Cholesterol Synthesis and Transport In Sertoli Cellsmentioning
confidence: 99%